Efeito dos dopantes nas propriedades estruturais e magnéticas do sistema Sn1-xMTxOy (MT = Fe, Ni, Co, Mn e Cr) - Cunha, Thiago Rodrigues da (2015)
In this work were investigated the synthesis of crystal systems of SnO and SnO2 in bulk and nanostructured form, pure and doped with different transition metals (TM = Fe, Co, Cr, Mn and Ni), using the thermal decomposition of compounds organometallic (DT) and co-precipitation (CP) methods. Through the technique of X-ray diffraction (XRD) combined with Rietveld refinement method of crystal structures by the use of free software tools DBWS 9807th, proved that the DT method revealed the formation of SnO with tetragonal symmetry, space group P4/nmm and mean crystallite size ranging from 4 to 16 nm, while the Co-precipitation method provided SnO2 samples with tetragonal symmetry, space group P42/mnm and crystallite sizes between 10 and 60 nm. To determine the optical band gap of some samples, absorbance measurements were performed as a function of wavelength in regions ranging ultraviolet to visible (UV-Vis), which were determined near of 4 eV for SnO2. From the magnetic point of view, the TM-doped samples were characterized by magnetization as a function of the temperature (MxT), which we can prove appropriate dilution of TM ions and extract the number of these ions that contribute paramagnetic form with values between 0.009 and 0.142% of the nominal value in SnO2 systems and values between 1.54 and 2.51% in the SnO systems, in addition to magnetization as a function of magnetic field measurements (MxH) reveal that for almost all systems examined at room temperature a ferromagnetic ordering in both compounds, with a reduction in the coercive field values with increasing in the MT concentration of approximate 300 to 0 Oe in the systems of SnO2 while in the SnO this magnitude reduces of approximate 40 to 5 Oe, such ordering can be attributed to interaction between diluted MT ions, provided by possible defects in the crystal structure.